ANALISIS PEMBIAYAAN MEKAAR PLUS SYARIAH PT. PERMODALAN NASIONAL MADANI MEKAAR CABANG RUPIT MUSI RAWAS UTARA - Hamidah, Nur; Saleh, Muhammad (STKIP Persada Khatulistiwa Sintang, 2023)
Mekaar syariah financing is financing to meet the need for increased production both quantitatively and qualitatively. The purpose of this research is to determine the analysis of Mekaar reguler Sharia financing at PT. Madani National Capital (PNM) Mekaar North Rupit Musi Rawas Branch, supporting and inhibiting factors. The method used is qualitative with data collection techniques using interviews, observation, and documentation. The data analysis techniques used are data reduction, data display and verification. Test the validity of the data using Triangulation. Research respondents consisted of: area heads, branch heads, deputy branch heads, FAO, accounts officers. The research results found that PT. PNM Mekaar Syariah North Rupit Musi Rawas Branch conducted a financing analysis in 2 stages. The first analysis is analysis of the financing process, which consists of 4 stages in the form of preparation, identification, analysis and verification, finally monitoring. The second analysis is analysis of customer needs, in this case PNM carries out analysis in the form of Working Capital Turn Over (WCTO), Project Cost, and based on the Cost Budget Plan (RAB).